2022
DOI: 10.3390/su14041973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thymol and Nanostructured Lipid Carriers (NLCs) Incorporated with Thymol as Antimicrobial Agents in Sausage

Abstract: The aim of this study was to evaluate the antimicrobial activity of thymol and thymol-loaded nanostructured lipid carriers (NLCs) on inoculated sausages at 4 °C over a period of 28 days. To this end, sausage samples containing 600 mg/kg thymol, 600 mg/kg thymol-loaded NLC, 600 mg/kg thymol + 60 mg/kg nitrite, and 600 mg/kg thymol-loaded NLC + 60 mg/kg nitrite were prepared, and each treatment was divided into three portions to be inoculated with S. aureus, E. coli, and C. perfringens (105.5 CFU/g). The mean di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For these reasons, there has also been a variety of recent research developing TH-loaded NLC structures providing antimicrobial and antioxidant activity. [73][74][75] In fact, those are all mainly applied to the food industry as antioxidants and preservatives. Although, these were all made of lipid mixtures of non-pure nature, where they also contained a variety of others nutritional ingredients inside its composition, such as proteins and sugars, among others, proving completely different characteristics than those for cosmetics applications.…”
Section: Dovepressmentioning
confidence: 99%
“…For these reasons, there has also been a variety of recent research developing TH-loaded NLC structures providing antimicrobial and antioxidant activity. [73][74][75] In fact, those are all mainly applied to the food industry as antioxidants and preservatives. Although, these were all made of lipid mixtures of non-pure nature, where they also contained a variety of others nutritional ingredients inside its composition, such as proteins and sugars, among others, proving completely different characteristics than those for cosmetics applications.…”
Section: Dovepressmentioning
confidence: 99%
“…NLC are another lipid nanosystem used to preserve meat products. A study that evaluated the antimicrobial effect of NLC incorporated with thymol (the main component of oregano, thyme, and rosemary EOs) on sausages inoculated with S. aureus , E. coli , and C. perfringes (10 5.5 CFU/g) found that thymol alone and the thymol-NLC decreased the growth of microorganisms most effectively in sausages with added nitrite [ 68 ].…”
Section: Nanosystems For Encapsulation Of Essential Oilsmentioning
confidence: 99%
“…A combination of EO-NE (cinnamon, cardamom, Chinese pepper, Tahiti lemon, and oregano) effectively reduced Clostridium sporogenes vegetative cells in processed mortadella meat products, in addition to providing antioxidant effects without changing product characteristics and prolonging shelf life [65]. The addition of thymol-NE in sausages effectively inhibited the growth of E. coli, S. aureus, and C. perfringens bacteria [73]. Fresh chicken treated with Zataria multiflora EO-NE coated with starch increased…”
Section: Current Use Of Nanoemulsion In Meat Productmentioning
confidence: 99%
“…Natural ingredients were chosen as an alternative to synthetic preservatives and to ease concerns about resistance to microbial pathogens [82]. Thymol NE can be used as an alternative to replacing nitrite as a preservative in sausages [73].…”
Section: Functionality Improvement Of Meat Productmentioning
confidence: 99%